2019
DOI: 10.1002/esp.4647
|View full text |Cite
|
Sign up to set email alerts
|

Decadal morphological evolution of the mouth zone of the Yangtze Estuary in response to human interventions

Abstract: The morphology of the Yangtze Estuary has changed substantially at decadal time scales in response to natural processes, local human interference and reduced sediment supply. Due to its high sediment load, the morphodynamic response time of the estuary is short, providing a valuable semi‐natural system to evaluate large‐scale estuarine morphodynamic responses to interference. Previous studies primarily addressed local morphologic changes within the estuary, but since an overall sediment balance is missing, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 64 publications
0
52
0
Order By: Relevance
“…Along with more than 50,000 other reservoirs in the catchment, the Three Gorges Dam has reduced downstream suspended sediment concentrations by 70 to 90% and induced major changes in sedimentation patterns in the estuary (Yang et al 2018a). The markedly reduced fluvial sediment loads have, as expected, resulted in recession of the Yangtze delta (Luo et al (2017), although impacts on the wider estuarine environment have not always been as anticipated (Zhu et al 2019). Indeed, accretion of mudflats has actually increased in many localities around the Yangtze estuary due to lower annual discharge and reduced flood frequencies (Hu et al 2019), a situation that has been further promoted through land reclamation (Sengupta et al 2019).…”
Section: Coastal and Estuarine Wetlands In The Anthropocenementioning
confidence: 86%
“…Along with more than 50,000 other reservoirs in the catchment, the Three Gorges Dam has reduced downstream suspended sediment concentrations by 70 to 90% and induced major changes in sedimentation patterns in the estuary (Yang et al 2018a). The markedly reduced fluvial sediment loads have, as expected, resulted in recession of the Yangtze delta (Luo et al (2017), although impacts on the wider estuarine environment have not always been as anticipated (Zhu et al 2019). Indeed, accretion of mudflats has actually increased in many localities around the Yangtze estuary due to lower annual discharge and reduced flood frequencies (Hu et al 2019), a situation that has been further promoted through land reclamation (Sengupta et al 2019).…”
Section: Coastal and Estuarine Wetlands In The Anthropocenementioning
confidence: 86%
“…Not surprisingly, bed erosion and reduction in suspended sediment concentration (SSC) have been observed in various regions of the Yangtze Estuary [1][2][3][4]. However, it has been suggested that there might be a morphological lag response to riverine sediment supply changes of about 10-30 years in seaward regions [5,6]. In this regard, it is important to conduct highresolution 10-30 years prediction of the response of the hydro-sediment-morphodynamic system in the Yangtze Estuary.…”
Section: Introductionmentioning
confidence: 99%
“…Over past decades, more than 50000 dams have been constructed and a large number of local engineering projects undertaken in the river basin and its estuary. Surveys have comprehensively examined decadal to seasonal erosion-deposition processes affecting geomorphic units within estuarine and offshore areas of the Yangtze subject to significant variations in water dynamics and sediment supply caused by intense human activities (Liu et al, 2009;Yang et al, 2011;Dai et al, 2013Dai et al, , 2014Dai et al, , 2016Du et al, 2016;Luan et al, 2016;Yang et al, 2016;Zhu et al, 2017;Mei et al, 2018;Zhu et al, 2019;Zhu et al, 2020). It has been established that certain of these morphological changes have led to practical problems, including migration of navigation features (Liu et al, 2009;Dai et al, 2013), increased risk of embankment failure related to water abstraction projects (Ou et al, 2013), and recession of saltmarsh-wetland systems (Wei et al, 2015;Gu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The latter processes are usually related to local erosion or deposition in estuarine systems, and are caused by variations in sediment load, runoff discharge and local hydrodynamics due to human interference. For example, reduction in fluvial sediment load due to the trapping effect of river dams has led to widespread recession of river deltas around the world (Rao et al, 2010; Maloney et al, 2018; Zhu et al, 2019), whereas runoff regulation of river dams has triggered depositional features (Frihy and Lawrence, 2004; Zamora et al, 2013) and altered spatial erosion–deposition distributions in estuaries (Zhu et al, 2017, 2018). Moreover, estuarine engineering projects interfere with local hydrodynamics and adjust nearby erosion–deposition patterns (Nitsche et al, 2007; Liu et al, 2009; Luan et al, 2016; El Jakani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation